Prebiotics and probiotics as alternatives to usage of antibiotics and coccidiostat for broiler chickens - Ajao, A.E.; Ademola, S.G; Oni , E.F; Ogunwande, A.I.; Mustapha, H.M.; Arasi, K.K.; Adio , A.A. (ADAN JOURNAL OF AGRICULTURE, 2026)
This study evaluated growth performance and nutrient digestibility of broiler chickens fed diets supplemented with prebiotics and probiotics as alternatives to antibiotics and coccidiostats. Three hundred and ninety-six (396), 7 days old Arbor Acres broiler chicks were randomly distributed into 9 treatments groups of 4 replicates each of 11 birds. Experimental diets were as follows: corn soybean meal-based diet was the Basal Diet (BD) which served as the control. Control = BD + Medicated Water “MW” (0.4g antibiotics plus 0.5g coccidiostat/L), T1 = BD + 0.5g probiotics/kg, T2 = BD + 2g prebiotics/kg, T3 = BD + 0.5g probiotics + 2g prebiotics/kg, T4 = BD + 1g probiotics + 4g prebiotics/kg, T5 = BD + 0.5g probiotics/kg + MW, T6 = BD + 2g prebiotics/kg + MW, T7 = BD + 0.5g probiotics + 2g prebiotics/kg + MW, T8 = BD + 1g probiotics + 4g prebiotics/kg + MW. All data collected were subjected to One Way and 2x2x2 factorial ANOVA at p≤0.050. The results showed that broiler starters in T3 (634.10, 25.17g), and those in T6 (670.35, 27.18g) significantly produced higher final body weight (FBW, P=0.0002), average daily weight gain (ADG, P=0.0003) than other groups. The best (P=0.002) FCR was noticed in starters in T6 (1.73) or T2 (1.71). Broiler finishers in T3 had the heaviest FBW (2464.50g, P=0.016), ADG (54.44g, P=0.010). Chickens in T2 had the highest (P<0.0001) digestibility in dry matter (96.27%), crude fibre (96.27%), ash (93.99%) and nitrogen free extract (99.80% in T4) with ether extract (86.01% in T3). It is concluded that supplementation of synbiotics of 0.5g probiotics and 2g/kg prebiotics as well as 2g prebiotics produced maximum FBW, ADG and optimum nutrient digestibility. It is therefore recommended that these two supplements at their dosage are best for optimum growth performance.